Guía para los suplementos de fibra - Wendy J. Dahl (EDIS)
Constipation is a common health concern that is commonly caused by low fiber intake. This 3-page fact sheet provides answers to common questions about fiber supplements. Written by Wendy J. Dahl and published by the UF Department of Food Science and Human Nutrition, May 2011.